2019
DOI: 10.1186/s11658-019-0137-1
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: MicroRNA-325-3p inhibits cell proliferation and induces apoptosis in hepatitis B virus-related hepatocellular carcinoma by down-regulation of aquaporin 5

Abstract: BackgroundHepatitis B virus (HBV) infection is acknowledged as the main cause of hepatocellular carcinoma (HCC). Moreover, previous studies have revealed that microRNAs (miRNAs) widely participate in regulation of various cellular processes, such as viral replication. Hence, the purpose of this study was to investigate the roles of aquaporin 5 (AQP5) and miR-325-3p in the proliferation and apoptosis of HBV-related HCC cells.MethodsAQP5 and miR-325-3p expression in both normal and HBV-HCC tissues or cells (both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…Hsa-miR-325 and hsa-miR-510-5p participate in tumor development (40)(41)(42)(43). Hsa-miR-325 has been identified as a potential biomarker in human bladder cancer and low expression of hsa-miR-325 was associated with poor overall survival in patients with bladder cancer (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hsa-miR-325 and hsa-miR-510-5p participate in tumor development (40)(41)(42)(43). Hsa-miR-325 has been identified as a potential biomarker in human bladder cancer and low expression of hsa-miR-325 was associated with poor overall survival in patients with bladder cancer (40).…”
Section: Discussionmentioning
confidence: 99%
“…Hsa-miR-325 has been identified as a potential biomarker in human bladder cancer and low expression of hsa-miR-325 was associated with poor overall survival in patients with bladder cancer (40). In addition, downregulation of hsa-miR-325 has been demonstrated to promote the progression of non-small cell lung cancer and HCC (41,42). Chen et al (43) found that hsa-miR-510-5p acted as a tumor suppressor in renal cell carcinoma by reducing cell proliferation, migration and inducing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that miR-325-3p was implicated in cellular processes in different types of diseases. For example, Zhang et al (21) reported that miR-325-3p decreases aquaporin 5 expression to confine hepatitis B virus replication in hepatocellular carcinoma. Another study investigating hypoxic-ischemic brain damage indicated that miR-325-3p aggravates rat neonatal hypoxia-ischemia brain injury by modulating aralkylamine N-acetyltransferase (22).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are endogenous, non-coding small RNAs which participate in posttranscriptional regulation by targeting the 3'-untranslated region (UTR) of mRNAs, causing degradation or translation suppressing of mRNAs, and act as suppressors or oncogenes in tumorigenesis [49][50]. In this study, miRNAs which may influence GOLGA8B expression were selected only when they were predicted by six algorithms.…”
Section: Discussionmentioning
confidence: 99%